National Consensus on Contraindications for Corneal Donation for Transplantation in Switzerland - Blaser, Frank; Immer, Franz; Kruegel, Nathalie; Franscini, Nicola; Tappeiner, Christoph; Rennesson, Christophe; Massa, Horace; Reinshagen, Helga; Früh, Beatrice; Kaufmann, Claude; Meneau, Isabelle; Said, Sadiq (Klinische Monatsblätter für Augenheilkunde, 2024)
Purpose To establish a national consensus on contraindications for corneal donation for transplantation in Switzerland.Methods Swisstransplant (SWT), the Swiss national foundation coordinating tissue and organ donations, convened a working group consisting of six national corneal surgeons and eye bankers and donation experts to create a contraindication list for corneal donation. The group reviewed available national and international guidelines and recommendations, while adhering to Swiss law and transplant regulations. In cases of opposing opinions, the group held follow-up meetings until a consensus was reached. A consensus was defined as agreement among all parties present.Results From March 2021 to November 2021, the study group held six meetings and created a standardized minimal contraindication list for corneal donation in Switzerland. Thanks to this list, SWT has created a mandatory working and documentation file for donor coordinators to use when evaluating multiorgan donors for corneal harvesting. The authors agreed that while the national consensus list provides standardized minimal contraindication criteria, local eye banks may choose to introduce additional, more rigorous criteria.Conclusion Given that corneal transplantation is the most commonly performed transplantation, establishing a consensus on contraindications is crucial for recipient safety. The creation of a consensus on contraindications for corneal donation in Switzerland is an essential contribution to fulfil the legal requirements concerning quality assurance and provides sufficient high-quality donor tissue within the country. Therefore, periodic review and revision of the consensus is considered critical.
Keywords: tissue donation; transplantation; corneal transplantation; expert meeting; consensus